Emigration and the Age Profile of Retirement among Immigrants - Cobb-Clark, D; Stillman, S (My University, 2008)
This paper analyzes the relationship between immigrants’ retirement status and the prevalence of return migration from the host country to their country of origin. We develop a simple theoretical model to illustrate that under reasonable conditions the probability of return migration is maximized at retirement. Reduced-form models of retirement status which control for the rate of return migration are then estimated using unique data on emigration rates matched to individual-level data for Australia. We find that immigrants, particularly immigrant women, are more likely to be retired than are native-born men and women with the same demographic, human capital, and family characteristics. Moreover, within the immigrant population, there is a negative relationship between the propensity to be retired and the return migration rate of one’s fellow countrymen, particularly amongst men. This link is strongest for those individuals who are at (or near) retirement age and among those with the highest cost of return migration. These results suggest that the fiscal pressures associated with aging immigrant populations vary substantially across origin countries.
IZA Discussion Paper
IZA Discussion Papers
Keywords: Ageing; Culture; Ageing -- Retirement; Culture -- Immigrants; Ageing; Culture and language; Ageing; Culture and identity; Culture, identity and language